Burst SCS Microdosing Is as Efficacious as Standard Burst SCS in Treating Chronic Back and Leg Pain: Results From a Randomized Controlled Trial. Issue 2 (19th November 2018) - Vesper, Jan; Slotty, Philipp; Schu, Stefan; Poeggel‐Kraemer, Katja; Littges, Heike; Van Looy, Pieter; Agnesi, Filippo; Venkatesan, Lalit; Van Havenbergh, Tony
Abstract : Introduction: The burst waveform, a recent innovation in spinal cord stimulation (SCS), can achieve better outcomes than conventional tonic SCS, both for de novo implants and as a salvage therapy. Burst stimulation delivers more energy per second than tonic stimulation, which is a consideration for battery consumption. The clinical effectiveness of an energy‐conserving strategy was investigated. Methods: Subjects were experienced users of BurstDR SCS for back and leg pain. Three 2‐week stimulation paradigms were presented in blinded random order: standard (continuously delivered) BurstDR, microdosing A: 5 sec of BurstDR alternating with 5 sec of no stimulation, and microdosing B: 5 sec of BurstDR alternating with 10 sec of no stimulation. The primary outcome for each paradigm was change in pain ratings, and secondary outcomes included changes in scores for quality of life, satisfaction, and preference. Results: Twenty‐five subjects assessed all three stimulation paradigms. There were no significant differences in pain (visual analog scale) or quality of life (EQ‐5D) when comparing standard burst outcomes with those of microdosing A and, separately, microdosing B. Microdosing paradigms were graded with slightly higher level of satisfaction and were generally preferred above standard burst stimulation. Discussion: These results suggest that the use of energy‐efficient burst microdosing stimulation paradigms with alternating stimulation‐on and stimulation‐off periods can provide clinically equivalent results to standard burst stimulation. This is important for extending SCS battery life. Further research is needed to comprehensively characterize the clinical utility of this approach and the neurophysiological mechanisms for the maintenance of pain relief during stimulation‐off periods.